Respuesta :
Answer:
9
Step-by-step explanation:
If 3 is added to the number: x + 3
b) ...and the sum is tripled..
"The sum" is "x + 3" so: 3(x+3)
c) ...the result is 27 more than the number.
27 more than the number is x + 27
d) Put it all together:
3(x + 3) = x + 27
Solve for x:
1) Distribute the left side of the equation:
3x + 9 = x + 27
2) Subtract x from each side of the equation:
2x + 9 = 27
3) Subtract 9 from each side of the equation:
2x = 18
4) Solve for x:
x = 9
Check:
1) x = 9
2) 3(x + 3) = x + 27
3) 3 ([9] + 3) = [9] + 27
4) 3(12) = 9 + 27
5) 36 = 36
Hello there! Hope you are having a nice day! :)
- First of all, let the number be t.
- Add 3 to the number:
- 3+t
- Now, triple the sum:
- 3(3+t)
- Now, the result is 21 more than the number:
- 3(3+t)=t+21
- Now, solve the equation for [tex]t[/tex]:
- [tex]\longmapsto\sf{3(3+t)=21+t}\\\longmapsto\sf{9+3t=21+t}\\\longmapsto\sf{9+3t-t=21}\\\longmapsto\sf{9+2t=21[/tex]
- [tex]\longmapsto\sf{2t=21-9}\\\longmapsto\sf{2t=12}\\\text{Divide both sides by 2 :}[/tex]
- [tex]\text{t=6}[/tex]
[tex]\huge\fbox{Answer:\:t=6}[/tex]
Hope it helps!
[tex]\rm{Stargazing{\bold{WithJoy:D}[/tex]